Acute port congestion and emissions exceedances as an impact of COVID-19 outcome: The case of San Pedro Bay ports - Luka Vukić; Kee-hung Lai (Journal of Shipping and Trade (JST), 2022)
In the second half of 2020, the shift in consumer demand and reduction in containership capacity, as a consequence of the COVID-19 pandemic, contributed to the disruption of the global supply chains, especially on the US West Coast. This article provides an environmental view of acute maritime congestion in Los Angeles and Long Beach anchorage areas aiming to calculate air emissions of anchored ships consistently in a specific month of the year and compare the dynamics of the emission levels with previous years. The findings determine the causes of the increased environmental pollution and conclude on the preservation measures improvement. CO2, SOx, NOx, PM10, and PM2.5 emissions are examined in this study, considering the statistical data on port performance, productivity and competitiveness elements, ship specifications and propulsion, and emission factors of principal pollutants. Results of our mathematical calculation showed an exponential increase of air emissions generated from ships' auxiliary engines and boilers in 2021, compared with the previous periods, reaching more than 45,000 tons of pollutants emitted in November (mainly carbon dioxide). The increased port congestion and pressure upon the environment and human health also exposed the vulnerability of the intermodal chain on the landside, manifested in higher utilization of trucking services inland, contributing to the additional growth of total emissions. The environmental degradation caused by the surge in demand for products carried by container ships coincides with increased social impacts and the requirement for investments in mitigation measures for emissions to reduce the harmful effects of shipping activities.
Keywords: 650; Air emissions; Port congestion; Anchored ships; San Pedro Bay; COVID-19